UPAYA MITIGASI BENCANA NON-STRUKTURAL DI DAERAH RAWAN BENCANA MELALUI PROGRAM KULIAH KERJA NYATA-PEMBERDAYAAN MASYARAKAT DESA BELANTING, KECAMATAN SAMBELIA - Pracoyo, Atas; Kusumah, Iqbal Firmana; Agustina, Erna; Sumiati, Sumiati; Fikri, Adam; Kurnita, Nila; Nopiyanti, Lina Yulia; Mussofa, Lalu Muhammad Assalin; Fanggidae, Gusti Ayu Anastasya Angline; Magfira, Baiq Nandia Rizki (Universitas Mataram, 2023)
Belanting Village is a settlement spanning 6,030 hectares located at the base of Mount Rinjani and situated at the easternmost tip of Lombok Island. The village boasts a picturesque landscape with rice fields and hills surrounding it. However, beneath this beauty, Belanting Village faces various challenges, one of which is natural disasters. This village falls within an area identified as prone to landslides according to Regional Regulation No. 12 of 2012 regarding the Spatial Plan of East Lombok Regency for the period 2012-2032. This is substantiated by a history of disasters covered by the mass media and testimonies from Belanting residents, ranging from flash floods, earthquakes, droughts, fires, and more. Given that a significant portion of the village's population consists of newcomers not accustomed to mountainous regions, there is a need to enhance the community's knowledge and understanding in facing disasters. It's crucial for them to know what actions to take, avoid, and how to ensure their safety in case of any unforeseen calamities. To address these challenges, the UNRAM PMD Community Service team has undertaken non-structural disaster mitigation measures. These activities are encompassed within a community service program known as